Comparative Genomic and Metabolomic Analyses of Two Pseudomonas aeruginosa Strains With Different Antifungal Activities - Wang, Shumin; Huang, Zhendong; Wan, Qing; Feng, Shuo; Xie, Xiaochen; Zhang, Ruiling; Zhang, Zhong (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa isolated from the plant rhizosphere has been widely used as an effective strain in biological control against plant disease. This bacterium promotes plant growth and protect plants against various phytopathogens through the production of phenazine metabolites. In this study, the strain P. aeruginosa Y12 with anti-Beauveria bassiana activity was isolated from the gut of housefly larvae. It was comparatively analyzed with the strain P. aeruginosa P18, which showed no anti-B. bassiana activity. Genomic and metabolomic methods were used to obtain a comprehensive understanding of the antimicrobial mechanism of Y12. After whole-genome resequencing of the two strains, a total of 7,087 nonsynonymous single-nucleotide polymorphisms (nsSNPs), 1079 insertions and deletions (InDels), 62 copy-number variations (CNVs) and 42 structural variations (SV) were found in both strains. Of these variations, 24 nsSNPs were found to be located on phenazine biosynthesis-related genes, which may influence the synthesis of phenazine derivatives. We analyzed the differentially abundant metabolites between Y12 and P18, and identified six bioactive compounds that could be associated with the antimicrobial activity of Y12. Additionally, we found that, unlike other previously reported rhizospheric P. aeruginosa strains, Y12 could produce both phenazine-1,6-dicarboxylic acid (PDC) and pyocyanin (PYO) at significantly higher concentrations than P18. As B. bassiana is an effective biological insecticide that can cause high mortality in adult houseflies but has little effect on housefly larvae, we believe that P. aeruginosa Y12, identified in housefly larvae but not in adults, serves as a defense mechanism in larvae and protects them from entomopathogenic fungal infections through the production of toxic metabolites.